Conference proceedings / International Conference Fluid Power 2017, September 14th - 15th, 2017, Maribor, Slovenia (University of Maribor Press, 2017)
The International Fluid Power Conference is a two day event, intended for all those professionally-involved with hydraulic or pneumatic power devices and for all those, wishing to be informed about the ‘state of the art’, new discoveries and innovations within the field of hydraulics and pneumatics. The gathering of experts at this conference in Maribor has been a tradition since 1995, and is organised by the Faculty of Mechanical Engineering at the University of Maribor, in Slovenia. Fluid Power conferences are organised every second year and cover those principal technical events within the field of fluid power technologies in Slovenia, and throughout this region of Europe. This year’s conference is taking place on the 14th and 15th September in Maribor. We wish all participants at the International Conference-Fluid Power 2017 continued successful professional work, and hope that we have yet again added another small piece within the mosaic of fluid power.